Impact of Management Support on the Functionality of Internal Control Units in Ensuring Compliance and Service Delivery - Awonke Geqeza (Journal of Business and Social Review in Emerging Economies)
Purpose: This study examines the impact of management support on the functionality of internal control units (ICU) in ensuring compliance and service delivery within the Eastern Cape Department of Rural Development and Agrarian Reform (ECDRDAR). Institutional Theory point of view is what this study is based on, more especial the New Institutional Sociology (NIS) perspective. The perspective of NIS provides a vigorous framework, which can be used to explain the formal adoption and practical implementation of internal control mechanisms within government departments, the study explores key challenges undermining ICU effectiveness.